2003
DOI: 10.1530/reprod/126.6.739
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation by leptin of the effects of fasting on ovarian function in hens (Gallus domesticus)

Abstract: Thirty-four-week-old laying hens received injections of recombinant chicken leptin to assess the role of leptin in avian ovarian function. In the first experiment, the hens (n = 60) were divided into three groups: (i) fed ad libitum; (ii) fasted; and (iii) fasted + leptin. Hens were fasted for 5 days and those treated with leptin received 250 g leptin kg −1 body weight twice a day, i.p. In the second experiment, the hens (n = 72) were divided into four groups: (i) fed ad libitum; (ii) fasted; (iii) fasted + le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Our results add an important strength to previous reports demonstrating chickens' response to exogenous administration of various leptins (Raver et al 1998, Denbow et al 2000, Paczoska-Eliasiewicz et al 2003, Lohmus et al 2004, Kuo et al 2005, by demonstrating for the first time a specific induction of signal transduction via CLEPR in response to human and frog leptins in vitro. It is possible that our inability to detect leptin activity in bird serum samples was due to below-detection threshold leptin levels, which could still be of physiological significance, rather than to a lack of natural ligand for CLEPR.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results add an important strength to previous reports demonstrating chickens' response to exogenous administration of various leptins (Raver et al 1998, Denbow et al 2000, Paczoska-Eliasiewicz et al 2003, Lohmus et al 2004, Kuo et al 2005, by demonstrating for the first time a specific induction of signal transduction via CLEPR in response to human and frog leptins in vitro. It is possible that our inability to detect leptin activity in bird serum samples was due to below-detection threshold leptin levels, which could still be of physiological significance, rather than to a lack of natural ligand for CLEPR.…”
Section: Discussionsupporting
confidence: 76%
“…Administration of this leptin in chickens resulted in inhibition of food intake (Dridi et al 2000, Cassy et al 2004. Additional studies have demonstrated the effect of this leptin on the immune response (Lohmus et al 2004), the onset of sexual maturity (PaczoskaEliasiewicz 2006), egg production during and after fasting (Paczoska-Eliasiewicz et al 2003), and downregulation of heat shock protein-70 (Figueiredo et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Ohkubo et al (2007) used a monoclonal antibody to part of ch-ObR to map it and found the short isoform in only a few tissues but the long isoform expressed more widely (mostly brain). These avian receptors use JAK-STAT (Adachi et al, 2008) and are expressed in ovary, brain and pituitary (Paczoska-Eliasiewicz et al, 2003). …”
mentioning
confidence: 99%
“…It is also involved in the regulation of energy stores, food intake and satiety (Bado et al, 1998;Brann et al, 2002). Leptin plays a role as activator of hypothalamic-pituitary-gonadal axis, inducing FSH-LH release and modulating steroidogenesis (McCann et al, 2001;Paczoska-Eliasiewicz et al, 2003). Thus, high leptin levels induce the production of gonadal steroids when a certain threshold of fatness is attained, acting as a permissive factor for reproduction (Brann et al, 2002).…”
Section: Hormones and Segregation Distortion: Patterns Of Primary Sexmentioning
confidence: 99%
“…Thus, high leptin levels induce the production of gonadal steroids when a certain threshold of fatness is attained, acting as a permissive factor for reproduction (Brann et al, 2002). Leptin levels in ovarian tissue increases during follicular maturation and ovulation in rats (Ryan et al, 2003), and leptin receptors have also been described in avian ovary (Ohkubo et al, 2000;Paczoska-Eliasiewicz et al, 2003). Moreover, leptin attenuates follicular atresia in chickens (Paczoska-Eliasiewicz et al, 2003).…”
Section: Hormones and Segregation Distortion: Patterns Of Primary Sexmentioning
confidence: 99%